Novel anti-dengue monoclonal antibody recognizing conformational structure of the prM-E heterodimeric complex of dengue virus - Puttikhunt C. (2014)
An interaction between the premembrane (prM) and envelope (E) glycoproteins as prM-E heterodimer is required for proper folding and transport of E during the formation and release of new flaviviral progeny. More evidence, however, is needed to confirm this interaction of prM and E during dengue virus replication. In this study, 2E11, a mouse monoclonal antibody (Mab) that specifically recognizes dengue prM-E heterodimeric complex in either intracellular or secreted dengue virions, was generated and characterized. In immunofluorescence and immuno-pull down assays, the Mab 2E11 recognized an epitope present in 293T transfectants that co-expressed prM and the full-length form of E in cis and in trans, but it failed to react with prM or E protein expressed individually. The reactivity of Mab 2E11 was diminished in transfected cells that co-express prM together with a truncated form of E lacking the 84-residue stretch at the C-terminal transmembrane region, presumably essential for prM and E interaction. The Mab 2E11 described in this study is a novel Mab with a unique capability in detecting the conformational structure of prM-E heterodimeric complex of dengue virus. It will be a new biological tool for identification and characterization of dengue prM-E heterodimeras well as virus maturation and export. © 2007 Wiley-Liss, Inc.